Building Equity Find Using LQ45 Stocks based on Business Cycle Issue in the period 2009-2013 - Sumaryana, Fitriana Dewi; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2015)
The growth of Mutual Funds in Indonesia is very rapid. This certainly has a positive influence on the Indonesian capital market. Mutual Fund is one instrument that has a quite large investment in the contribution of investment in the capital market. Referring to the Capital Market Law No. 8, 1995, article 1, paragraph (27) defined that the Mutual Fund is a vehicle used to collect funds from public investors to be invested in a portfolio of securities by the investment manager. From there, this final project provides an alternative to invest in mutual fund shares that contain any stocks that may provide better performance in the current economic conditions and how best portfolio of these stocks.In this final project, a conceptual framework is the stock selection, and composition of the portfolio return. Historical stock price data used are LQ-45. To create a portfolio, Excel Solver Ad-In is used to optimize the proportion of each stock. In addition, this study uses the business cycle as issues relating to the investment world. In different business cycles, the growing sector in general different.The approach used is the rate of profit (expected return) and the level of risk (standard deviation) generated from each portfolio are formed. Stocks are selected based on criteria are stocks in the index option LQ-45 and then projected by the method of regression for the next five years to see the performance in the future. Optimization aims to maximize portfolio returns using an efficient barrier specified, where in this thesis is the maximum return, the minimum standard deviation, beta value, and the maximum Sharpe Ratio.The conclusion of this final project is to construct optimal equity fund that can survive or perform well during periods of recession.Â Keywords:Â  mutual funds, equity fund stock selection, optimization of stock, the business cycle.Â